1978
DOI: 10.1073/pnas.75.8.3993
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lipid A and endotoxin in serum by mass spectroscopy

Abstract: ABSTRACrA quantitative technique for determining lipid A content of endotoxin added to serum by combined gas chromatography-mass spectrometry is described. This MATERIALS AND METHODS Serum Samples. New Zealand white rabbits weighing approximately 2 kg, and not fed overnight, were used. Blood was obtained by heart puncture under sterile conditions. Blood was also obtained aseptically from human volunteers by venipuncture. Serum was separated by centrifugation and stored in pyrogen-free tubes at -200.Solvents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…The 3-OH FAs (usually of 10-to 18-carbon chain lengths) have been suggested as chemical markers for LPS in mammalian samples. Low concentrations of 3-OH FAs have been found in normal human sera and plasma (3,4 ). Recently, the same 3-OH FAs were identified in rat blood, and because the concentrations were approximately the same in germ-free as in conventional rats, they were assumed to originate mainly from mitochondrial ␤-oxidation of endogenous FAs (5 ).…”
Section: © 2003 American Association For Clinical Chemistrymentioning
confidence: 94%
See 1 more Smart Citation
“…The 3-OH FAs (usually of 10-to 18-carbon chain lengths) have been suggested as chemical markers for LPS in mammalian samples. Low concentrations of 3-OH FAs have been found in normal human sera and plasma (3,4 ). Recently, the same 3-OH FAs were identified in rat blood, and because the concentrations were approximately the same in germ-free as in conventional rats, they were assumed to originate mainly from mitochondrial ␤-oxidation of endogenous FAs (5 ).…”
Section: © 2003 American Association For Clinical Chemistrymentioning
confidence: 94%
“…Interestingly, Limulus activity in plasma from patients with meningococcal septicemia showed a close quantitative association with the 3-OH FA results. In earlier studies (3,15 ), convincing dose-response relationships were found between serum concentrations of 3-OH FAs and added amounts of LPS. However, it should be noted that these studies were performed using GLC-MS analysis in the selected-ion monitoring mode, a method that provides high sensitivity but may lack specificity in sample matrices that are chemically complex.…”
Section: Fig 1 Examples Of Glc-msms Profiles Of 3-oh Fas In Serum (mentioning
confidence: 99%
“…They may thus produce false positive or false negative results ( 9 ). Quantitation of 3HM by GC/MS or GC/MS/MS corresponds to the direct measurement of LPS mass ( 8,10,11 ), but the detection of small amounts of 3HM in complex media is restricted by the limited amounts of lipid-rich samples that can be loaded on GC columns.…”
Section: Hplc/ms/msmentioning
confidence: 99%
“…However, viable bacteria were not detected (using classical microbiological culture) in the lunar material when it was first brought by the Apollo missions (Oyama et al, 1970). Unfortunately, chemical methods that detect dead bacterial remnants, or non-culturable bacteria, were in a primitive stage of development at that time (Maitra et al, 1978;Fox et al, 1980Fox et al, , 1993Fox et al, , 1995Fox et al, , 1996Findlay et al, 1983;Saraf and Larsson, 1996;Saraf et al, 1999;Bal and Larsson, 2000;Kozar et al, 2000).…”
Section: Plans To Visit Mars To Collect Samples For Life Detection Stmentioning
confidence: 99%
“…However, most environmental organisms are non-culturable and remain undetected. Analytical microbiology techniques (primarily GC-MS) detect not only viable bacteria, but also their nonviable cell envelope remnants when present in complex biological matrices (Maitra et al, 1978;Fox et al, 1980;Findlay et al, 1983;). More recently, gas chromatography tandem mass spectrometry (GC-MS/MS) has been proven to be capable of detecting terrestrial bacterial markers at minute concentrations in environmental and clinical samples (Fox et al, 1995(Fox et al, , 1996Saraf and Larsson, 1996;Saraf et al, 1999;Bal and Larsson, 2000;Kozar et al, 2000).…”
Section: Chemical Markers For Bacteriamentioning
confidence: 99%